Effects of Gut Microbiota on Host Adaptive Immunity Under Immune Homeostasis and Tumor Pathology State - Li, Yanan; Ye, Zixuan; Zhu, Jianguo; Fang, Shuguang; Meng, Lijuan; Zhou, Chen (Frontiers in Immunology, 2022)
Gut microbiota stimulates and shapes the body's adaptive immune response through bacterial components and its active metabolites which orchestrates the formation and maintenance of the body's immune homeostasis. In addition, the imbalances in microbiota-adaptive immunity contribute to the development of tumor and the antitumor efficiency of a series of antitumor therapies at the preclinical and clinical levels. Regardless of significant results, the regulation of gut microbiota on adaptive immunity in immune homeostasis and tumors need a more thorough undersanding. Herein, we highlighted the comprehensive knowledge, status and limitations in the mechanism of microbiome interaction with adaptive immunity, and put forward the prospect of how to translate these insights in inhibiting tumor progression and enhancing the efficacy of anti-tumor interventions.